Spatial Distribution of Methanesulphonic Acid in the Arctic Aerosol Collected during the Chinese Arctic Research Expedition - Peipei Ye; Zhouqing Xie; Juan Yu; Hui Kang (Atmosphere, 2015)
Methanesulphonic acid (MSA, mainly derived from marine biogenic emissions) has been frequently used to estimate the marine biogenic contribution. However, there are few reports on MSA over the Arctic Ocean, especially the central Arctic Ocean. Here, we analyzed MSA in aerosol samples collected over the ocean and seas during the Chinese Arctic Research Expedition (CHINARE 2012) using ion chromatography. The aerosol MSA concentrations over the Arctic Ocean varied considerably and ranged from non-detectable (ND) to 229 ng/m3, with an average of 27 ± 54 ng/m3 (median: 10 ng/m3). We found the distribution of aerosol MSA exhibited an obvious regional variation, which was affected by biotic and abiotic factors. High values were generally observed in the Norwegian Sea; this phenomenon was attributed to high rates of phytoplankton primary productivity and dimethylsulfide (DMS) fluxes in this region. Concentrations over the pack ice region in the central Arctic Ocean were generally lower than over the open waters at the ice edge in the Chukchi Sea. This difference was the mainly caused by sea ice. In addition, we found that higher MSA concentrations were associated with warmer sea surface temperature (SST).